Effects of formulation of soilless growth media from Azolla pinnata sp on water absorption, water loss, and water retention - Shamsudin, Rosnah; Azhari, Nor Aziatul Azidah; Kasim, Susilawati; Rahmat, Muhammad Ammar Syaheed (HH Publisher, 2021)
Most plants require soil as a growth media. Soilless media has been introduced to overcome the lack of soil for plant cultivations. An Azolla cube was developed as soilless growth media with nutrient-rich and water-storing capabilities through the usage of Azolla pinnata sp. Azolla cube is a new research product, providing an alternative to the existing products, such as Midorie Pafcal and Jiffy-7 pellets. This research introduced four samples of Azolla cubes at different formulations to evaluate the performance of the cubes on water absorption, water loss, and water retention. This product was developed by using two types of binder method: tapioca starch (Cassava starch) and Bentonite clay. Based on the results, sample C held an estimation of 5.94 g ± 0.01 of 10 g of water within 6 hours at room temperature while that of Sample A, B, and D was 5.45 g ± 0.01, 3.37 g ± 0.01, and 4.70 g ± 0.01, respectively. Sample C also lost an estimation of 2.56 g ± 0.01 of water within 2 days of observation. The results also showed that sample C had the highest percentage of moisture content (15.4%) after undergoing four stages of applied pressure, 0 kPa, 1 kPa, 33 kPa, and 1500 kPa, for the water retention test, in which the value of water movement remained constant. In conclusion, Azolla cube was shown to be capable of providing the nutrients needed for plants and absorbing more water compared to the current products.